Revision history of "L(-n)=(-1)^nL(n)"

Jump to: navigation, search

Diff selection: Mark the radio boxes of the revisions to compare and hit enter or the button at the bottom.
Legend: (cur) = difference with latest revision, (prev) = difference with preceding revision, m = minor edit.

  • (cur | prev) 00:39, 25 May 2017Tom (talk | contribs). . (342 bytes) (+342). . (Created page with "==Theorem== The following formula holds: $$L(-n)=(-1)^{n}L(n),$$ where $L(n)$ denotes the $n$th Lucas number. ==Proof== ==References== * {{PaperReference|A...")